Ectoparasitic chiggers (Acari: Trombiculidae, Leeuwenhoekiidae), lice (Phthiraptera), and Hemiptera (Cimicidae and Reduviidae) from South Carolina, U.S.A. - Reeves, Will K.; Durden, Lance A.; Wrenn, William J. (Zootaxa, 2004)
We report on the distribution of 15 chiggers, 31 lice of mammals, and 7 blood feeding hemipteran species in South Carolina. Some of these arthropods are vectors of pathogens to humans and domestic animals. Both Triatoma lecticularia and T. sanguisuga were reported from houses and these bugs are potential vectors of Trypanosoma cruzi. We also report on the continued presence of the bed bug, Cimex lectularius, in homes across the state. In addition we found the lice Haematopinus suis, Neohaematopinus sciuropteri, Pediculis humanus, Polyplax spinulosa, and Trichodectes canis, all of which are vectors or intermediate hosts of human or animal pathogens.